Survey of Accounting - Carl Warren (Cengage Learning, Inc, 2007)
Survey of Accounting 3e, is designed for a one-term introductory accounting course. It provides an overview of the basic topics in financial and managerial accounting, without the extraneous accounting principles topics that must be skipped or otherwise modified to fit into a one-term course. Written for students who have no prior knowledge of accounting, the text emphasizes how accounting reports are used by managers, investors, and other business stakeholders